(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Overweight and obesity have emerged as alarming public health concerns. Many contributing factors for body weight gain are present among young-aged populations. The purpose of this study was to determine the prevalence of overweight and obesity in young adults after the COVID-19 pandemic and the risk factors linked with it. This research was carried out from September 2023 to January 2024, focusing on young adults in Dhaka city. A standard questionnaire was designed for collecting data. Body weight and height were measured by an electronic weighing machine and measuring tape, respectively, to calculate the BMI of the participants. The association between factors and obesity and overweight was evaluated using the chi square test and the Fisher test of exactness. Three hundred seventeen (317) young adults were enrolled in the study. 13.9% (n = 44) and 3.2% (n = 10) of the study population were found to be overweight and obese, respectively. A family history of obesity was found to be significantly associated with being obese-overweight (p = 0.002) and identified as a high-risk factor for overweight-obesity (OR = 2.596, CI = 1.481–5.900). Overweight-obesity had a significant association with the concentration problem while working (p = 0.015), and overweight-obesity was found to be a risk factor in this regard (OR = 2.754, CI = 1.182– 6.419). Inadequate sleep duration and late-night sleeping habits were found to be risk factors for overweight and obesity (OR = 1.665, CI: 0.853–3.253; OR = 1.276, CI: 0.703–2.313, respectively). Appropriate measures should be followed to reduce the burden caused by overweight and obesity among young adults. Bangladesh Pharmaceutical Journal 27(2): 182-192, 2024 (July)